Performance Practice of Brian Cherney’s Music: Interviews with Marina Thibeault, Julia Den Boer, and Paul Vaillancourt - Huang, Aiyun (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2017)
The composition and performance practice of the Canadian composer Brian Cherney’s music is contextualized in interviews with violist Marina Thibeault, pianist Julia Den Boer, and percussionist Paul Vaillancourt. These three musicians performed major works by Cherney in “Illuminations: Brian Cherney at 75” to celebrate the work and life of the composer. All three interviewees analyze the challenges presented by Cherney’s scores and discuss the ways they found inspiration in the interpretation of the music.